INOVASI PEMASARAN JASA PENDIDIKAN SEBAGAI STRATEGI TRANSFORMASI MUTU DAN DAYA SAING SEKOLAH: Marketing Innovation in Educational Services as a Strategy for School Quality Transformation and Competitiveness - Anggriani, Wita; Aglesia, Ade Sonni; Fathurrochman, Irwan (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This study aims to develop an innovative educational service marketing model to enhance school quality and competitiveness. The primary focus of this research is to explore various innovative marketing strategies, such as digital marketing, branding, collaboration with local communities, and improved customer service, that play a role in increasing community participation and strengthening the relationship between schools and their surrounding environment. The findings reveal that digital marketing is effective in accelerating information dissemination, enhancing two-way communication, and expanding community involvement in educational quality development. However, the main challenges faced are technological disparities and resistance to change, which require strategic solutions to optimize the implementation of innovative marketing. This article provides both practical and theoretical contributions to innovative marketing-based educational management aimed at improving school quality and competitiveness.